Penerapan model word square Untuk Meningkatkan Pemahaman konsep ppadda mata pelajaran PKn di kelas v SDN sukadaya 01 kabupaten Bekasi - Dilla, dillawardatulhamro; Victorynie, Irnie (Pedagogik : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research is based on the problem of low understanding of concepts in class V of SDN Sukadaya 01 Bekasi Regency. The problems are: 1) The PKn score in class V is relatively low compared to other classes and subjects. 2) The understanding of the concept of PKn is low, this can be seen from students who are not able to understand the material that has been taught.3) Students in class V have difficulty giving examples related to the concept of PKn. 4) Students in class V have difficulty classifying the material given.5) Students in class V have difficulty making conclusions. In overcoming these problems, the Word Square learning model was implementea which aims to improve the understanding of the concept of PKn for grade V students of SDN Sukadaya 01 Bekasi Regency. The research method used is Classroom Action Research (PTK) which consists of 2 cycles, with 27 students and each cycle consists of 3 meetings. Data collection in this study uses a. Data collection in this study uses a written test data collection technique. The success criterion in this study is 70% with a KKM score of 70. The results of this study show that the increase in students' understanding of concepts in each cycle is 52% in the first cycle of classicai provisions with an average score of 74 and in the second cycle the classical completeness increases to 85% with an average score of 82. Based on this data, the learning model can increase the understanding of the concept of class V PKn by 38%. Thus, it can be concluded that the Word Square learning model can improve the understanding of the concept of PKn class V SDN Sukadaya 01 Bekasi Regency.